Influência do padrão de radiação na inversão da forma completa da onda baseada nos métodos do gradiente - Vasconcelos, Adna Grazielly Paz de (2018)
The recovery of multiple classes of parameters through full-waveform inversion (FWI) presents problems related with unbalanced update directions of the misfit functional gradient, due to crosstalk between different classes of parameters. The analysis of Fréchet derivatives and radiation pattern of each parameter class is presented as an alternative to the Hessian due to its high computational cost. This work aims to evaluate the sensitivity of FWI by analyzing the amplitude distribution of scattered fields as a function of the scattering angle, for elastic homogeneous and acoustic non-homogeneous models. The results showed that, for non-homogeneous models, the radiation patterns differ considerably from those presented in the literature for homogeneous models. The radiation pattern depends on the parameterization and background model, then it is repeatedly modified during inversion. Analogous to the radiation pattern, the amplitudes of the Fréchet derivatives for non-homogeneous models do not exhibit the same distribution observed for homogeneous models. As a consequence, the radiation patterns and their Fréchet derivatives, when evaluated in non-homogeneous models, could support the definition of a suitable data-driven workflow for multiparameter FWI. Thus, it is possible to measure the sensitivity of the observed data to different physical properties, reducing the crosstalk between parameters and improving the subsurface illumination in target area.